수능 영어 문항 유형간 응집력과 어휘정보 분석 - 최민주(Minju Choi); 김정렬(Jeong-ryeol Kim) (한국콘텐츠학회 논문지, 17(12), 2017)
The aim of this study was to analyze cohesion and word information among different types of questions in the English reading section of the College Scholastic Ability Tests (CSAT). The types of questions were divided into three categories: macro reading, micro reading, and indirect writing. Reading texts from 1994 to 2017 CSAT were analyzed by Coh-Metrix, an automated evaluation program of text and discourse. The findings of this study indicated that there were statistical differences among the three categories of questions for noun overlap, stem overlap, adversative and contrastive connective, additive connective, pronoun incidence, age of acquisition, concreteness for content word, imagability, and meaningfulness. The information of the findings bore pedagogic implications for developing textbooks, questions for CSAT, and reading strategies by students. 본 연구는 대학수학능력시험 영어영역 읽기지문의 문항 유형별 응집력과 어휘정보를 파악하기 위해 코퍼스 기반 분석을 실시하였다. 본 연구에서는 한국교육과정평가원에서 제시하는 여섯 가지의 문항유형을 세가지의 범주, 즉 맥락읽기, 세부읽기, 간접쓰기로 나누어 분석하였다. 이를 위해 처음 수능이 실시된 1994학년도부터 2017학년도까지의 수능 영어영역의 읽기지문의 코퍼스를 구축한 후, 코메트릭스 3.0을 활용하여 해당 코퍼스를 분석하여 각 문항들의 응집력과 어휘정보의 차이를 살펴보았다. 연구 결과 표층응집성 지표에서는 명사중복 측정치와 어간중복 측정치에서 통계적으로 유의미한 차이를 보였다. 연결사 지표에서는 역접의 연결사와 추가의 연결사에서 통계적으로 유의미한 차이를 보였다. 어휘정보 지표의 결과에서는 대명사의 발생정도, 습득나이 측정치, 내용어의 구체성 측정치, 심상성 측정치, 유의미성 측정치에서 통계적으로 유의미한 차이를 보였다. 이러한 문항유형간 응집력과 어휘정보 분석에 대한 정보는 교과서 집필 및 수능시험 출제에 활용될 수 있을 것이며, 학생들이 직접적으로 활용할 수 있는 읽기전략으로 활용 될 것으로 기대된다.